Efeitos do envelhecimento e do exercício físico sobre o sistema cardiovascular de indivíduos saudáveis - Melo, Ruth Caldeira de (Universidade Federal de São Carlos, 2008)
The ageing process is known to affect different tissues and systems. It is well-established that age-associated changes in cardiovascular structure and function are related to the risk of cardiovascular diseases. Because of the vast amount of cardiovascular modifications observed with ageing, the present study focused on three important topics: heart rate variability (HRV), blood pressure variability (BPV) and endothelial dysfunction. Furthermore, we also investigated the effects of physical activity (endurance and strength) on the autonomic control of heart rate (HR), which might be used as non-pharmacological therapy. Thirty five young subject between 18 and 30 years old (14 sedentary men, 5 sedentary women and 16 active men) and thirty eight middleaged/older subjects between 55 and 70 years old (16 sedentary men, 14 sedentary women and 8 active men) were studied. In addition, the subjects are distributed among 3 different studies. In the first one, the effects of the ageing process and active life-style on the autonomic control of HR were investigated in young and middleaged/older subjects. Electrocardiogram was recorded during 15 minutes of rest and 4 minutes of controlled breathing (5 to 6 cycles/min) in the supine position. HR and RR intervals were analyzed by time and frequency domain methods. The active groups presented lower HR and higher HRV (time domain) than the sedentary groups, whereas both middle-aged/older groups showed lower HRV (frequency domain). Additionally, interaction between ageing and life-style effects was observed for respiratory sinus arrhythmia (ASR) indexes (calculated during the controlled breathing test). The sedentary middle-aged/older group presented lower ASR magnitude than the other groups studied. The results suggest that ageing reduces HRV, however, regular physical activity improves vagal modulation on the heart and, consequently, attenuates the effects of ageing on the autonomic control of HR. In the second study, we aimed to investigate if strength training is able to improve cardiac autonomic control in healthy middle-aged/older men. HRV was evaluated before and after 12 weeks of isokinetic eccentric strength training (2days/week, 2-4 sets of 8-12 repetitions at 75-80% peak torque), involving knee flexion and extension. Strength training decreased the systolic blood pressure and increased the torque. However, an autonomic imbalance towards sympathetic modulation predominance was induced by an unknown mechanism. In the third study, we evaluated the effect of ageing on the BPV and endothelial function. We also sought for correlations between increased BPV and impaired endothelium dependent-dilation (EDD) in the middle-aged/older group. Intra-brachial artery BPV and conduit vessel EDD (brachial artery flow-mediated dilation, FMD) were determined in healthy young and middle-aged/older subjects. Moreover, endothelial function of resistance vessels was evaluated by venous occlusion plethysmoghaphy in the middle-aged/older group. The young group presented lower systemic oxidative stress, lower systolic BPV and higher FMD compared with the middle-aged/older group. After split this group according to the BPV, lower FMD was observed in the middleaged/older group with higher BPV. In addition, FMD was inversely correlated to BPV. The lower BPV group showed a great reduction (55%) in the forearm blood flow responses when NG-monometyl-L-arginine (nitric oxide inhibitor) was co-infused with acetylcholine (vs 14% in the higher BPV group). The results suggest that ageing process increases BPV and reduces endothelial function. Additionally, middle-aged/older subjects with higher BPV also have impaired EDD compared with their peers with lower BPV. General Conclusions: the results from the studies described above suggest that ageing process causes decrease of HRV, increase of BPV and decrease of endothelial function. Moreover, aerobic exercise has a cardioprotector effect, since it was able to attenuate the ageing effects on the cardiac vagal modulation. This same benefit, however, was not observed after 12 weeks of eccentric strength training. On the other hand, the strength training program performed by healthy older subjects modified the sympato-vagal balance toward the sympathetic modulation. Finally, systolic BPV oscillations seem to have a narrow relationship with vasodilation mediated by nitric oxide. Then, more studies are needed to clarify the cause-effect relation between those important variables.
Keywords: Envelhecimento; Sistema cardiovascular; Exercícios físicos; Variabilidade da frequência cardíaca; Arritmia sinusal respiratória; Atividade física aeróbia; Treinamento de força; Exercício isocinético; Variabilidade da pressão arterial; Ageing; Heart rate variability; Respiratory sinus arrhythmia; Aerobic exercise; Strength training; Isokinetic exercise; Blood pressure variability; Endothelium dependent dilation; Endothelial function; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL